+0  
 
0
297
1
avatar+176 

https://vle.mathswatch.co.uk/images/questions/question2452.png

jakeharris02  Nov 4, 2017

Best Answer 

 #1
avatar+628 
+1

I use a^2 + b^2 = c^2  (26 - 11)^2 + 8^2 = x^2, x = 17 ab = 17

 

Using a^2 + b^2 = c^2 again, 17^2 + 12^2 = x^2  x=square root of 433

supermanaccz  Nov 4, 2017
 #1
avatar+628 
+1
Best Answer

I use a^2 + b^2 = c^2  (26 - 11)^2 + 8^2 = x^2, x = 17 ab = 17

 

Using a^2 + b^2 = c^2 again, 17^2 + 12^2 = x^2  x=square root of 433

supermanaccz  Nov 4, 2017

15 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.